2015
DOI: 10.1186/s40695-015-0002-y
|View full text |Cite
|
Sign up to set email alerts
|

Depression in the menopause transition: risks in the changing hormone milieu as observed in the general population

Abstract: There is accumulating evidence but no definitive answers about the incidence of depressed mood in the menopause transition and its association with the changing hormonal milieu. While a changing hormonal milieu is the natural condition for all women, only a minority of mid-life women experience debilitating depressive symptoms or clinical depression. This review focuses on associations between depressed mood and the menopause transition, primarily as identified in longitudinal, population-based studies in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 119 publications
2
31
0
2
Order By: Relevance
“…In the analyses presented here, depressed mood severity reported for a 24 h period was not related to any of the MT markers. Although prior research has provided limited evidence linking endocrine changes and the MT stages to depressive symptoms and also to episodes of major depressive disorder among women with no prior history of depression, Freeman’s recent review concluded that the contribution of the changing endocrine milieu to the development of depressive symptoms was small [21]. She reminded us that only a minority of women experience debilitating depressive symptoms during this part of the lifespan and that hormonal change is not the only factor to consider in disentangling the complex pathways to depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the analyses presented here, depressed mood severity reported for a 24 h period was not related to any of the MT markers. Although prior research has provided limited evidence linking endocrine changes and the MT stages to depressive symptoms and also to episodes of major depressive disorder among women with no prior history of depression, Freeman’s recent review concluded that the contribution of the changing endocrine milieu to the development of depressive symptoms was small [21]. She reminded us that only a minority of women experience debilitating depressive symptoms during this part of the lifespan and that hormonal change is not the only factor to consider in disentangling the complex pathways to depression.…”
Section: Discussionmentioning
confidence: 99%
“…There was not a significant relationship between hot flashes and depressed mood over the past 24 h in the diary-based data reported here. In contrast, Freeman’s review [21] indicated that although the association between hot flashes and depressive symptoms predominantly measured with the CES-D was confirmed, the direction of the relationship was unclear and evidence for a relationship between hot flashes and major depressive disorder was much less clear. Although hot flashes predicted negative mood on the next day in SWAN daily diary data, negative mood did not predict hot flashes on the subsequent day [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Попри відомі дані про динаміку гормональних зрушень, механізми, що спричинюють зміни безпосередньо в яєчниках, є недоведеними [2]. Середній вік припинення МФ у світі коливається залежно від рівня економічного розвитку держави в межах 49-52 роки [3].…”
Section: вступunclassified
“…Depression is the most common of all the psychiatric disorders, and it is the main clinical manifestation of menopausal depression. In the National Comorbidity Survey, major depression is more ordinary in women than in men until late life, with a lifetime prevalence of 21% compared to 12% for men [1]. It was found that estrogens have intense effect on symptoms of depression [2].…”
Section: Introductionmentioning
confidence: 99%